2008
DOI: 10.4102/sajip.v34i2.725
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Orientation to Life Questionnaire (OLQ) in a chemical factory

Abstract: The objectives of this study were to assess the psychometric properties of the Orientation to Life Questionnaire (OLQ) and to investigate the differences in sense of coherence among demographic groups in a chemical factory environment. The OLQ and a biographical questionnaire were administered to chemical factory employees (N = 583). A three-factor model (manageability, meaningfulness and comprehensibility) was confirmed through structural-equation modelling. From the original 29-item OLQ, an 11-item OLQ and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Originally, according to Antonovsky, a general SOC construct that can often be arranged according to three SOC components exists -namely, comprehensibility, manageability and meaningfulness. He did later, however, suggest that these three theoretical components should not be considered as subscales of the SOC measure and, based on a review of several studies, concluded that a single factor is more likely to result from factor analysis (Van Schalkwyk & Rothmann, 2008). Muller (2007) also commented on studies confirming high intercorrelations among the three components.…”
Section: Factor Analysis Of Olq-13 Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Originally, according to Antonovsky, a general SOC construct that can often be arranged according to three SOC components exists -namely, comprehensibility, manageability and meaningfulness. He did later, however, suggest that these three theoretical components should not be considered as subscales of the SOC measure and, based on a review of several studies, concluded that a single factor is more likely to result from factor analysis (Van Schalkwyk & Rothmann, 2008). Muller (2007) also commented on studies confirming high intercorrelations among the three components.…”
Section: Factor Analysis Of Olq-13 Datamentioning
confidence: 99%
“…Similarly, Gropp et al (2007) and Van Schalkwyk and Rothman (2008) referred to SOC as a general orientation to one's environment that serves as a source of general resistance resources in order to deal with life demands. As such, SOC facilitates one's ability to perceive and control the environment for meaningful and appropriate action (Van Schalkwyk & Rothmann, 2008).…”
Section: Psychological Wellness and Sense Of Coherencementioning
confidence: 99%
See 3 more Smart Citations